El debido proceso en el procedimiento del cobro coactivo de las entidades territoriales (2018)
The administrative coercive collection, understood as the ability of management to collect the debts itself in his favor, violates the constitutional principles of impartiality, legal certainty and transparency because the enforcement officer acts as judge and jury, without allowing the administered, within the same process, to come up to a review of the proceedings advanced, since only by means of the contentious jurisdiction in the process of annulment and restoration of law could request review of the proceedings conducted by the administration.